1983
DOI: 10.3133/pp1263
|View full text |Cite
|
Sign up to set email alerts
|

Application of total-count aeroradiometric maps to the exploration for heavy-mineral deposits in the coastal plain of Virginia, with a section on field-spectrometer-data reduction

Abstract: Total-count contoured aeroradiometric maps for the Coastal Plain of Virginia were used in an effort to locate economic heavy-mineral placer deposits. The principle behind this approach is that heavymineral suites commonly contain radioactive minerals that, if the concentration of heavy minerals is exposed at or within inches of the surface, enable the deposit to be located by use of airborne instruments because of its radiometric contrast with the host sediment. Detailed and regional geologic maps, soil maps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
1
15
0
Order By: Relevance
“…:fine-sand facies deposits (Grosz, 1983). Other anomalies in the Lower Cretaceous to Pleistocene sediments in the Coastal Plain of Virginia indicate important areas for exploration.…”
Section: The Eastern Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…:fine-sand facies deposits (Grosz, 1983). Other anomalies in the Lower Cretaceous to Pleistocene sediments in the Coastal Plain of Virginia indicate important areas for exploration.…”
Section: The Eastern Statesmentioning
confidence: 99%
“…Between 1975 and1983, this U.S. Department of Energy program acquired stream sediment geochemistry and airborne spectral gamma-ray radiation data for the conterminous 48 States and Alaska. · The HSSR, one component of the NURE program, entailed collection and analysis of samples of sediment (stream, soil, talus, playa, and others), ground water, surface water, and vegetation to determine concentrations of uranium and other selected elements (Arendt and others, 1980).…”
Section: The Nure Program Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Grosz (1983) carried out an exploration assessment of the HMS deposits along the coastal plain of Virginia. His study employed total-count aeroradiometric maps followed by field checking of 80 identified anomalies by ground radiometric surveys and sediment samples.…”
Section: Brink Depositmentioning
confidence: 99%
“…A study of the HMS deposits of the coastal plain in Virginia by Grosz (1983) applied total-count aeroradiometric maps as a technique to explore for HMS. His study found that when surveyed on the ground, HMS accumulations produce radiometric spectra of intermediate to low intensity with thorium producing the strongest radiation component and with lesser contributions from uranium and potassium.…”
Section: Previous Mineral Resource Assessments In the Atlantic Coastamentioning
confidence: 99%